La educación sexual como eje transversal, para coadyuvar a la formación integral de las niñas y niños del 7mo grado paralelo “A”, de la escuela fiscal mixta “Zoila María Astudillo Celi”, del barrio Celi Román, parroquia Sucre, cantón y provincia de Loja, período académico 2014-2015 - Agila Benítez, Johanna Leonor (2016)
This research paper called sex education as transverse axis to contribute to the integral development of girls and boys 7th grade PARALLEL "A" SCHOOL OF THE JOINT FINANCIAL "ZOILA MARIA CELI ASTUDILLO" DEL BARRIO CELI Roman PARISH SUCRE, canton province of Loja, ACADEMIC PERIOD 2014-2015, has the general objective to promote sex education as a central focus to contribute to the integral formation of students in the seventh grade of the Fiscal School "Zoila Maria Astudillo Celi" city Loja. It corresponds to a type of descriptive study and experimental pre- since worked with a certain group of students, in which methods were used, comprehensive, analytical, synthetic, with the technique of direct observation and the application of a survey to the teachers, parents and students. For the research work intervened 22 human talents, one teacher and 21 students. In this way it was possible to obtain timely information for the development of research, resulting in that students have many shortcomings, difficulties and unknowns from sexual education. Teachers speak very little and work of these issues within classes, not known strategies for addressing sexuality; Likewise, parents do not have adequate and accurate knowledge to discuss this subject with their children. Finally we conclude that sex education is a transverse axis, which should be given greater priority and importance as it allows us to develop fully.